EXPERIENCE OF CONDUCTING MASTER CLASSES ON THE DEVELOPMENT OF FINE MOTOR SKILLS IN A CHILDREN'S POLYCLINIC - Любовь Николаевна Симакова; Марина Юрьевна Галактионова; Людмила Николаевна Сифоркина; Анастасия Викторовна Гордиец; Ирина Викторовна Турлак; Марина Вениаминовна Лавыгина; Анастасия Олеговна Симакова; Максим Викторович Сифоркин (The Publishing House Medicine and Enlightenment, 2019)
This article provides information about the organization, preparation and the conduct of training sessions in the form of master classes on the development of fine motor skills in a children's polyclinic, where children, their parents and medical workers will become familiar with the means and techniques of fine motor development taking into account the age and the presence of diseases.